2004
DOI: 10.1017/s0033291704003721
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of homocysteine, folic acid and vitamin B12 with depression in a middle-aged community sample

Abstract: Low folic acid and high homocysteine, but not low vitamin B12 levels, are correlates of depressive symptoms in community-dwelling middle-aged individuals. The effects of folic acid and homocysteine are overlapping but distinct.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(97 citation statements)
references
References 27 publications
6
87
2
2
Order By: Relevance
“…The protective association between serum folate and depressive symptoms in this study has been observed in many (Bjelland et al, 2003;Morris et al, 2003;Ramos et al, 2004;Sachdev et al, 2005;Dimopoulos et al, 2007;Kim et al, 2008), but not all (Penninx et al, 2000;Tiemeier et al, 2002) studies. The association was consistently found among populations with an average age of less than 70 years (Bjelland et al, 2003;Morris et al, 2003;Sachdev et al, 2005;Dimopoulos et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
See 4 more Smart Citations
“…The protective association between serum folate and depressive symptoms in this study has been observed in many (Bjelland et al, 2003;Morris et al, 2003;Ramos et al, 2004;Sachdev et al, 2005;Dimopoulos et al, 2007;Kim et al, 2008), but not all (Penninx et al, 2000;Tiemeier et al, 2002) studies. The association was consistently found among populations with an average age of less than 70 years (Bjelland et al, 2003;Morris et al, 2003;Sachdev et al, 2005;Dimopoulos et al, 2007).…”
Section: Discussionsupporting
confidence: 62%
“…Administration of folic acid was also shown to be associated with early recovery from depression (Fava et al, 1997;Taylor et al, 2003), suggesting a therapeutic importance of this nutrient. A protective role of folate in depression has been further supported by various epidemiologic studies, in which either dietary folate intake (Tolmunen et al, 2003(Tolmunen et al, , 2004aSanchez-Villegas et al, 2006;Murakami et al, 2008) or blood folate concentrations (Bjelland et al, 2003;Morris et al, 2003;Ramos et al, 2004;Sachdev et al, 2005;Dimopoulos et al, 2007;Kim et al, 2008) or SNPs involved in folate metabolism (Gilbody et al, 2007a) was used as the exposure index. In a recent meta-analysis of 11 studies, persons with low levels of serum, low red blood cell or low intake of folate had a 1.4 times increased risk of depressive symptom, compared with those with high folate status (Gilbody et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations